Intensified peginterferon α-2a dosing increases sustained virologic response rates in heavy, high viral load hepatitis c genotype 1 patients with high low-density lipoprotein - Harrison, Stephen A.; Abdurakhmanov, Djamal; Shiffman, Mitchell L.; Bakulin, Igor; Mazur, Wlodzimierz; Rodriguez-Torres, Maribel; Silva, Giovanni Faria [UNESP]; Cheinquer, Hugo; Messinger, Diethelm; Connell, Edward V.; McKenna, Michael; Tatsch, Fernando; et al. (Wolters Kluwer, 2013)
BACKGROUND AND GOAL: Patients infected with hepatitis C virus (HCV) with elevated low-density lipoprotein (LDL) levels achieve higher sustained virologic response (SVR) rates after peginterferon (PegIFN)/ribavirin treatment versus patients with lower LDL. Our aim was to determine whether SVR rates in patients with low/elevated LDL can be improved by dose intensification. STUDY: In PROGRESS, genotype 1 patients with baseline HCV RNA≥400,000 IU/mL and body weight ≥85 kg were randomized to 48 weeks of 180 μg/wk PegIFN α-2a (40 kDa) plus ribavirin (A: 1200 mg/d; B: 1400/1600 mg/d) or 12 weeks of 360 μg/wk PegIFN α-2a followed by 36 weeks of 180 μg/wk, plus ribavirin (C: 1200 mg/d; D: 1400/1600 mg/d). This retrospective analysis assessed SVR rates among patients with low (<100 mg/dL) or elevated (≥100 mg/dL) LDL. Patients with high LDL (n=256) had higher baseline HCV RNA (5.86×10 IU/mL) versus patients with low LDL (n=262; 4.02×10 IU/mL; P=0.0003). RESULTS: Multiple logistic regression analysis identified a significant interaction between PegIFN α-2a dose and LDL levels on SVR (P=0.0193). The only treatment-related SVR predictor in the nested multiple logistic regression was PegIFN α-2a dose among patients with elevated LDL (P=0.0074); therefore, data from the standard (A+B) and induction (C+D) dose arms were pooled. Among patients with low LDL, SVR rates were 40% and 35% in the standard and induction-dose groups, respectively; SVR rates in patients with high LDL were 44% and 60% (P=0.014), respectively. CONCLUSIONS: Intensified dosing of PegIFN α-2a increases SVR rates in patients with elevated LDL even with the difficult-to-cure characteristics of genotype 1, high baseline viral load, and high body weight. Copyright © 2013 by Lippincott Williams & Wilkins.
Keywords: chronic hepatitis C; low-density lipoprotein; pegylated interferon; ribavirin; sustained virologic response; low density lipoprotein; peginterferon alpha2a; peginterferon alpha2a plus ribavirin; adult; aged; alopecia; anemia; anorexia; arthralgia; asthenia; body weight; chill; coughing; depression; diarrhea; drug fatality; drug safety; drug tolerability; dry skin; fatigue; female; fever; genotype; hepatitis C; human; injection site erythema; insomnia; irritability; major clinical study; male; myalgia; nausea; neutropenia; priority journal; pruritus; rash; relapse; side effect; treatment duration; treatment response; virus load; vomiting; weight reduction; xerostomia; Adolescent; Adult; Aged; Aged, 80 and over; Antiviral Agents; Body Weight; Cholesterol, LDL; Dose-Response Relationship, Drug; Double-Blind Method; Drug Therapy, Combination; Female; Genotype; Hepacivirus; Hepatitis C; Humans; Interferon-alpha; Logistic Models; Male; Middle Aged; Polyethylene Glycols; Randomized Controlled Trials as Topic; Recombinant Proteins; Retrospective Studies; Ribavirin; RNA, Viral; Treatment Outcome; Viral Load; Young Adult